New Perspectives in Sustainable Aquaculture - Caterina Longo; Cataldo Pierri (Journal of Marine Science and Engineering, 2023)
The strong growth of the aquaculture industry can represent a serious threat to aquatic ecosystems and requires the development of new strategies to control and minimize the impact of such activities on the structure and function of biological communities [...]